Binding of Collagen by Canine Blood Platelets - Kay, W. W; Swanson, R; Chong, G; Kurylo, E; Bharadwaj, B. B (Thrombosis and Haemostasis, 1977)
The binding of 125I-collagen (tropocollagen) by canine blood platelets occurred in a concentration-dependent manner but no saturation effect could be observed. The binding of collagen was not entirely specific for platelets since various eucaryotic and procaryotic cells quantitatively bound collagen as well or better.The temporal response to added collagen appeared to be binding, 3H-serotonin release, and finally platelet aggregation. Non-polymerizing salt-soluble tropocollagen was bound as well as acid-soluble tropocollagen, however neither 3H-serotonin release nor platelet aggregation occurred. Furthermore, the binding activity was not destroyed by treatment with collagenase, galactose oxidase and glucose oxidase, nor by periodate oxidation.Platelet aggregation closely paralleled acid soluble collagen polymerization and both events were equally inhibited by arginine; however, arginine did not interfere with collagen binding. Scanning electron microscopy revealed an unusual morphological platelet response to collagen and platelets appeared to be nucleation sites for collagen polymerization.